MASA KEEMASAN KEUANGAN ISLAM (PERSPEKTIF SEJARAH) - Nur Rahmah; Munadi Idris (Jurnal Ekonomi Bisnis Syariah, 2019)
The development of Islamic finance began at the beginning of the coming of Islam which at the time of the Prophet saw. by implementing a payment system for zakat, kharaj, fai, and ghanimah and establishing Baitul Maal as the center of the state treasury. The Baitul function increases the experience of development as banking functions today. During the reign of the Abbasid dynasty using a check system and currency transfers can be done at the Baitul Mal institution. The purpose of this research is to describe the management of the Islamic finance of the Messenger of Allah, to complete the future of the Khufaurrasyidin and reach the golden peak during the Abbasid Dynasty. This research is a type of literature research that aims to describe the Islamic financial system during the early arrival of Islam until it reached its peak in the reign of the Abbasid dynasty. Data on the development of the Islamic financial system is appropriate in the work of scholars, researchers and historians who write about the development of Islamic finance until the future of Islamic packaging. The conclusion of this study about the development of Islamic finance is based on the development of the Baitul Maal which was first established by the Messenger of Allah. Seeing the storage of the state and continuing in the chaos of the Rashidin Baitul Maal was built in several areas during the reign of the Baitul Maal Abbasid Dynasty the enactment of Dinar and Dirham as a means of transnational transactions.